PENGARUH KOMPETENSI, KOMPENSASI FINANSIAL DAN MOTIVASI KERJA PADA KEPUASAN KERJA KARYAWAN TAKE JAPANESE RESTAURANT LEGIAN KUTA BADUNG BALI - Putra, I Putu Purnama; Mujiati, Ni Wayan (E-Jurnal Manajemen, 2016)
Job satisfaction is a positive attitude of people in general to the work performed. So that employees have high job satisfaction. The purpose of this study was to determine the effect of competence, financial compensation and motivation to work on job satisfaction karyawan.Penelitian is done in Take Japanese Restaurant naughtiest, samples taken as much as 49 respondents with pusposive sampling method. Collecting data by questionnaires by using a 4-point Likert scale, measuring 19 indicators. The analysis technique used is linear regression analysis berganda.Hasil these studies show that the variable competence, financial compensation and motivation positive effect on employee satisfaction Take Japanese Restaurant Badung. These results shows if the competence, financial compensation and motivation of the respondents perceived increase will make the respondents perceived job satisfaction also increased.
Keywords: kompetensi; kompensasi finansial; motivasi kerja; kepuasan kerja